Oxidative Stress and Apoptosis in Disk Abalone (Haliotis discus hannai) Caused by Water Temperature and pH Changes - Min Ju Kim; Jin A Kim; Dae-Won Lee; Young-Su Park; Jun-Hwan Kim; Cheol Young Choi (MDPI AG, 2023)
Ocean warming and acidification can induce oxidative stress in marine species, resulting in cellular damage and apoptosis. However, the effects of pH and water temperature conditions on oxidative stress and apoptosis in disk abalone are poorly understood. This study investigated, for the first time, the effects of different water temperatures (15, 20, and 25 °C) and pH levels (7.5 and 8.1) on oxidative stress and apoptosis in disk abalone by estimating levels of H2O2, malondialdehyde (MDA), dismutase (SOD), catalase (CAT), and the apoptosis-related gene caspase-3. We also visually confirmed apoptotic effects of different water temperatures and pH levels via in situ hybridization and terminal deoxynucleotidyl transferase dUTP nick end labeling assays. The levels of H2O2, MDA, SOD, CAT, and caspase-3 increased under low/high water temperature and/or low pH conditions. Expression of the genes was high under high temperature and low pH conditions. Additionally, the apoptotic rate was high under high temperatures and low pH conditions. These results indicate that changes in water temperature and pH conditions individually and in combination trigger oxidative stress in abalone, which can induce cell death. Specifically, high temperatures induce apoptosis by increasing the expression of the apoptosis-related gene caspase-3.